Peningkatan Strategi Pemasaran Online Produksi Jamu Tradisional - Yani, Yepita Ghufiromah; Wafa, Zaenal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to improve the online marketing strategy of traditional herbal medicine products from